EFEKTIFITAS LAYANAN KONSELING KELOMPOK UNTUK MEREDUKSI DEGRADASI MORAL PADA REMAJA - Lisa Sis Mona; Silvianetri Silvianetri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Adolescence is a very important period in the process of individual growth and development. Adolescence is ideally filled with fun things, learning about healthy relationships, learning to explore one's abilities, and planning future goals. In fact, nowadays we often see news on television about unhealthy teenage relationships, inappropriate clothing, brawls between students, bullying in schools, disrespect for parents, disrespect for teachers and even drug use and promiscuity which causes pregnant out of wedlock, we also encounter this behavior in the school environment. This behavior can be said to be moral degradation or moral decline in teenagers. The role of a guidance and counseling teacher is very important to prevent or reduce moral degradation by providing one of the services in Guidance Counseling, namely Group Counseling services. This research aims to examine the effectiveness of group counseling services in reducing moral degradation in adolescents, especially students at school. This research uses qualitative research. The conclusion of this research is that guidance and counseling teachers can use group counseling services as an effort to reduce the moral degradation of teenagers, especially students at school.